Penerapan Pelatihan dan Pengembangan Karyawan terhadap Peningkatan Kinerja Karyawan di PT BPR Dana Nagoya - Nelson, Alden; Agatha, Jennifer (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Employee training and development is a very important investment for companies to improve the quality of Human Resources (HR). Therefore, the purpose of this study is to evaluate the impact of training and development on improving employee performance at PT BPR Dana Nagoya by using qualitative data collection methods and primary data sources, specifically observation and interviews. The results of the implementation of this activity show that this training and development program not only improves employee performance, but also helps overcome the problem of external employee recruitment at PT BPR Dana Nagoya, and helps develop employee knowledge and abilities. Thus, this program will indirectly improve the overall performance of the company.